2022
DOI: 10.3390/microorganisms10030498
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/Calmodulin-Dependent Protein Kinase II Inhibits Hepatitis B Virus Replication from cccDNA via AMPK Activation and AKT/mTOR Suppression

Abstract: Ca2+/calmodulin-dependent protein kinase II (CaMKII), which is involved in the calcium signaling pathway, is an important regulator of cancer cell proliferation, motility, growth, and metastasis. The effects of CaMKII on hepatitis B virus (HBV) replication have never been evaluated. Here, we found that phosphorylated, active CaMKII is reduced during HBV replication. Similar to other members of the AMPK/AKT/mTOR signaling pathway associated with HBV replication, CaMKII, which is associated with this pathway, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…[ 31 ] However, one study revealed that CaMKKII and AMPK form a positive feedback loop, where AMPK overexpression increased CaMKII activity, and AMPK inhibitors also blocked CaMKII phosphorylation. [ 45 ] In our present study, we used a CaMKKII inhibitor (STO‐609) to investigate whether the activation of CaMKKII phosphorylation is mainly due to the direct activating effect of Kahweol or the AMPK‐CaMKKII positive feedback loop. The results showed that STO‐609 significantly inhibited the phosphorylation activation of AMPK by Kahweol.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] However, one study revealed that CaMKKII and AMPK form a positive feedback loop, where AMPK overexpression increased CaMKII activity, and AMPK inhibitors also blocked CaMKII phosphorylation. [ 45 ] In our present study, we used a CaMKKII inhibitor (STO‐609) to investigate whether the activation of CaMKKII phosphorylation is mainly due to the direct activating effect of Kahweol or the AMPK‐CaMKKII positive feedback loop. The results showed that STO‐609 significantly inhibited the phosphorylation activation of AMPK by Kahweol.…”
Section: Discussionmentioning
confidence: 99%
“…Then, HepG2 or HEK293T cells were transduced with supernatant containing pseudoviral particles and shRNAs (shPIN1 or shPIN4) or control shRNA, as mentioned above, and then selected with puromycin. Stable HepG2-hNTCP-C9 cells were generated as described previously using lentiviral expression vector pCDH-CMV-hNTCP-C9-EF1-Puro ( Kim et al., 2022 ). HepG2-hNTCP-C9-derived PIN1 knockdown cells were generated as described above.…”
Section: Methodsmentioning
confidence: 99%
“…HBV particles were prepared from culture supernatants of HepAD38-pCDH, HepAD38-Pin1, and HBV-infected HepG2-hNTCP-C9 cells as described previously ( Watashi et al., 2013 ; Ko et al., 2014 ; Kim et al., 2022 ), with minor modifications. Culture supernatants comprising F-12 DMEM (11320-033, Gibco) supplemented with 10% FBS, 1% penicillin/streptomycin, 5 μg/ml insulin (#I9278, Sigma-Aldrich), and 50 μM hydrocortisone hemisuccinate (#1319002, Sigma-Aldrich) were collected 4 days after tetracycline removal, centrifuged briefly, and filtered through a 0.45 μm bottle top filter to remove cell debris.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistence of HBV is attributable to its covalently closed circular DNA (cccDNA). cccDNA acts as a transcription template on a chromosome in the infected nucleus, encodes a pregenomic RNA (pgRNA) encapsulated by HBV polymerase, pgRNA is reverse transcribed by HBV DNA polymerase into partially double-stranded relaxed circular DNA (rcDNA) 1 , 2 . The viral genome has four overlapping open reading frames encoding the HBV core protein (HBc), the envelope protein, viral polymerase, reverse transcriptase, and regulatory HBX which is regarded as an oncoprotein.…”
Section: Introductionmentioning
confidence: 99%